MRI findings before and after prolapse surgery. (May 2014) - Alt, Céline D; Brocker, Kerstin A; Lenz, Florian; Sohn, Christof; Kauczor, Hans-Ulrich; Hallscheidt, Peter
Background: Therapeutical outcome after prolapse surgery is evaluated using a standardized grading system based on maximum prolapse extent, which might not provide the full picture of the patient's subjective outcome. We therefore applied an evaluation method, which is detached from a grading system. Purpose: To evaluate the impact of pelvic organ mobility in dynamic magnetic resonance imaging (MRI) before and after mesh-repair surgery in patients with symptomatic pelvic organ prolapse. Material and Methods: To obtain measurements, we performed parasagittal T2-weighted turbo spin echo sequence at rest (TR, 3460 ms; TE, 85 ms; matrix, 512; slice thickness [ST], 5 mm), parasagittal T2-weighted true fast imaging with steady-state precession (TrueFISP) single-shot sequence during straining (TR, 397.4 ms; TE, 1.5 ms; matrix, 256; ST, 8 mm), and parasagittal T2-weighted TrueFISP sequence at maximum strain (TR, 4.3 ms; TE, 2.15 ms; matrix, 256; ST, 5 mm) at 1.5 T MRI. Pelvic organ prolapse (anatomical landmarks: bladder, cervix, pouch, rectum) was measured perpendicularly with reference to the pubococcygeal and the midpubic line. Pelvic organ mobility was defined as the difference between the measured distance at rest and at maximum strain for each anatomical landmark. All patients underwent mesh-repair procedure. Eighty patients could be included in this short-term follow-up study. Due to the physical diagnosis of pelvic organ prolapse, 51 underwent anterior mesh repair, 16 underwent posterior mesh repair, and 13 underwent total mesh repair. Surgery was performed by one surgeon, using mesh implants from several manufacturers. Results: Median values of maximum organ prolapse for bladder, cervix, pouch, and rectum preoperatively were 2.54 cm, 0.33 cm, 2.47 cm, and 0.32 cm, respectively, and 12 weeks postoperatively 0.87 cm, −1.79 cm, 1.49 cm, and 0.49 cm, respectively. Highly significant improvement ( P  < 0.001) of pelvic organ mobility was observed in the treated compartment at 4- and 12-week follow-up. Physical evaluation 12 weeks after mesh-repair showed an asymptomatic POP-Q stage I, if any. Conclusion: Dynamic MRI is useful in visualizing the maximum extent of pelvic organ prolapse, as the evaluation of pelvic organ mobility documents the intraindividual therapeutic outcome detached from a grading system based on maximal prolapse values.